The Role of Key Opinion Leaders in Increasing Brand on Social Media - Patricia Felicita Ardyan; Mirelle; Valen; Irmawan Rahyadi; Ricardo Indra (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the digital era, social media and Key Opinion Leaders (KOLs) play a crucial role in promoting beauty brands like Scarlett. This research examines the role of Key Opinion Leaders (KOLs) in enhancing the marketing communication strategy of the Scarlett brand on Instagram and YouTube. Using qualitative research with a case study approach, this study explores how KOLs influence consumer perceptions and behaviors through content creation, storytelling, and engagement. Data were gathered through in-depth interviews with KOLs who collaborate with Scarlett, and content analysis of posts shared across both platforms. The findings reveal that KOLs play a vital role in shaping brand image and generating high engagement rates, particularly when their personal values align with the brand’s messaging. On Instagram, visual appeal and personal narratives significantly capture audience attention, while on YouTube, informative and emotionally resonant videos strengthen consumer connections. The research further highlights the effectiveness of interactive features such as polls and Q&A sessions in increasing audience participation and trust. Although KOLs primarily build brand awareness rather than drive direct sales, their influence fosters curiosity and encourages product trials. The study concludes that KOLs are integral to modern marketing communication strategies, providing authenticity and credibility.